T(x) phase diagram of the CuSbS2–CuInS2 system and solubility limit of Sb in CuInS2. Issue 9 (21st August 2013) - Korzun, B. V.; Gavrilenko, A. N.; Fadzeyeva, A. A.; Ignatenko, O. V.; Maroz, I. I.; Sobol, V. R.; Rusu, M.; Klenk, R.; Merschjann, C.; Schedel‐Niedrig, Th.; Lux‐Steiner, M. Ch.
<x xml:space="preserve">Abstract</x> The starting ternary compounds CuInS2 and CuSbS2 and alloys of the CuSbS2 ‐ CuInS2 system with the molar fractions of CuInS2 (x) equal to 0.05, 0.15, 0.25, 0.375, 0.50, 0.625, 0.75, 0.85, and 0.95 were prepared and the phase relations in this system were investigated by X‐ray powder diffraction, optical microscopy, scanning electron microscopy, and differential thermal analysis. It was shown that the T‐x phase diagram of the CuInS2 – CuSbS2 system has eutectic character with the eutectic temperature of 807 K. The limits of solubility are 0.059 molar fractions for CuSbS2 in CuInS2 and 0.038 molar fractions for CuInS2 in CuSbS2. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>